Job Satisfaction and Stress among Primary School Teachers During COVID-19 - Ponnusamy, P.; Sankar, Sumitha (THE PRIMARY TEACHER, 2022)
Due to the global challenge of COVID-19 pandemic issues, academic processes at all levels of the educational system were collapsing. Students and teachers faced challenges in terms of teaching and learning methods and face-to-face interactions. Without any preparatory processes, the teachers and students were forced to use online transitions. Due to the change of practices, teachers experienced a high level of stress and were not satisfied mostly with the new online practices. The present study aims to measure the level of job satisfaction and stress among primary school teachers during the COVID-19 pandemic period. To do this, a survey was conducted to a sample of 180 primary school teachers who were given a questionnaire—Teacher Job Satisfaction and Stress Scale (TJSSS) and Teacher to collect the required data. Results found that there is a significant relationship between the job satisfaction and stress of primary school teachers